Thoracoscopic Repair of Congenital Diaphragmatic Hernia - Wagner, Richard; Mayer, Steffi; Feng, Xiaoyan; Gosemann, Jan-Hendrik; Zimmermann, Peter; Lacher, Martin (European Journal of Pediatric Surgery, 2020)
The surgical management of patients with congenital diaphragmatic hernia (CDH) is challenging and ever changing. It requires the highest expertise not only on the surgical level but also of neonatologists and anesthesiologists. In selected patients traditional open surgery is increasingly replaced by thoracoscopic CDH repair in many centers worldwide. Despite obvious and well-described advantages of the minimally invasive approach like a shorter ventilatory time, less pain, a shorter hospital length of stay, and a better cosmesis, important controversies remain. This review discusses hot topics of minimally invasive CDH repair, such as extracorporeal membrane oxygenation, hypercapnia/acidosis, patch repair, surgical training, and recurrence.
Keywords: minimally invasive surgery; congenital diaphragmatic hernia; review